Unsuspected uterine sarcomas undergoing morcellation: A retrospective multicenter study. Issue 1 (March 2018) - Wong, Avelyn WY; Tsaltas, Jim; Manley, Tom R; Ratner, Roni T; Yim, Cheryl CM; Barel, Oshri
Objective: To evaluate the prevalence of unsuspected uterine sarcomas undergoing morcellation at the time of hysterectomy or myomectomy. Design: A retrospective cohort study. Settings: A teaching health service in Melbourne, Australia, consisting of four hospitals which provide gynecology and gynecology oncology services including one tertiary referral center. Population: All women undergoing any form of hysterectomy or myomectomy from 1998 to 2016. Methods: Patient demographics and the presence of morcellation were collected. All cases of confirmed uterine sarcomas were further examined and their histological subtype, patient demographics, preoperative investigations, and surgical indication were also identified. Results: A total of 7584 cases were studied. Overall, 33 uterine sarcomas were identified. Of these, seven cases were unsuspected malignancies. All seven cases were leiomyosarcomas. None of the malignant specimens underwent morcellation. The overall prevalence of uterine sarcomas in the total study population was 0.44%. The rate of unsuspected uterine sarcomas in women undergoing hysterectomy or myomectomy for presumed benign indications was 0.13% or 1 in 769. The rate of unintended morcellation of a uterine sarcoma in our center was 0%. The diagnosis of endometrial sarcoma was prompted by endometrial sampling in 58% of the cases when performed. Conclusion: The risk of inadvertent morcellation of unsuspected uterine sarcomas is low. Patients should be appropriately selected with adequate investigations and a detailed history and examination prior to surgery. Further studies are needed to identify effective preoperative screening methods for uterine sarcomas.